Elections And Centralism In Peru: Some Reflections - Mac Gregor, Felipe (Universidad del Pacífico, 1980)
Paper read by the author in the Maes-Heller Auditorium of Universidad del Pacífico in March 25th of the present year, on the occasion of Jorge Basadre´s book presentation.